DENSITY OF Vibrio sp. BACTERIA AND HETEROTROFIK BACTERIA IN DUMAISEA WATEROF RIAUPROVINCE - Aan Deni Masrudy; Feliatra Feliatra; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted from April until May 2018. The purpose of this study was to calculate the density of Vibrio sp. bacteria insea water of Dumai,to determine the ratio of Vibrio sp.toheterotrophicbacteria to examine the resistence of Vibrio sp. to antibiotics. In this study the determination of sampling points using purposive sampling method, was set into three sampling points for each station. Density total of Vibrio sp. and heterotrofik bacteria by using spread plate count method. The result showed that density Vibrio sp.ranged from 1.3 x 103 - 1.6 x 103 CFU / ml. the haignest number of Vibrio sp. wasfound in stations 4, and the lowest was in station 5.  The total number of heterotrophic bacteria ranged from 7.37 x 106 - 10.38 x 106 CFU / ml. the highest number of heterotrophic was found in station 4 in the lowest was in station 5. The hignest percentange ratio of the density of Vibrio sp.to heterotrophic bacteria was in station 5 0.0178% and the lowest was in station 1 0.0144%. resistance ofVibrio sp. toward Chloramphenicol as antibiotic tested indicatedthat 31 isolates were categorized into intermediate with the inhibition zone ranged from 12-19.8 mm, and 1 isolate was sensitive with the inhibition zone was 21 mm. Toward antibiotics penicilin and isoniazid, all bacterial isolates were resistant with the inhibition zone ranged from 1.6 - 9 mm and 0.9 - 6.2 mm, respectively. Keyword: Density, Vibrio sp,Heterotrophic Bacteria, Antibiotics